Understanding of Job Insecurity, Quality of Work Environment, and its Implications for Employee Turnover Intention: A Study of Indonesian State-Owned Companies (SOEs) in the Field of Electronics for Facilities and Infrastructure - Maulita, Tanzila Salma; Winarno, Alex (PT FORMOSA CENDEKIA GLOBAL, 2024)
The phenomenon of employee turnover is triggered by high turnover intention in employees caused by internal or external factors. This study aims to determine how job insecurity and work environment can contribute to the phenomenon of turnover intention in Indonesia State-Owned Companies (SOE’s) in the field of electronics for industry and infrastructure. By using descriptive causality analysis and quantitative approach. Data from 250 samples were collected through questionnaires and tested with multiple linear regression analysis with the help of SPSS version 29 software to determine the magnitude of variable contributions. The results showed that job insecurity partially influenced turnover intention positively but insignificantly, while workers' surrounding conditions significantly influenced turnover intention negatively. The influence of job insecurity and work environment together affect 8.1% of employee turnover intention in the state-owned company.